Applied energy : an introduction - Abdullah, Mohammad Omar. (Boca Raton, FL : Taylor & Francis, 2013)
'Focusing on renewable energy technologies, energy conversion, and conservation and the energy industry, this volume discusses energy applications in small-medium enterprises, solar energy, hydro and wind energy, nuclear energy, hybrid energy, and energy sustainability issues. The author lists the key aspects of applied energy and related studies, taking a question-based approach to the material that is useful for both undergraduate students and to postgraduates who want a broad overview of energy conversion. In addition to illustrations, the text contains numerous worked examples, case studies, and homework problems'--
Includes bibliographical references and index.
Keywords: Power resources; Energy transfer; Industries -- Power supply